A clinical utility of neutrophil lymphocyte ratio as an independent predictor of systemic lupus erythematosus disease activity - Abira, Mahmuda; Islam, Mohammad Sirajul; Ahmad, Rahnuma; Sultana, Farhana; Akter, Tahmina; Islam, Md Daharul; Akhter, Qazi Shamima (Bangladesh Journal of Medicine, 2023)
Background: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease and is associated with considerable morbidity. The neutrophil-to-lymphocyte ratio (NLR) has been chosen as a potential marker of inflammation in SLE. Objective: To evaluate the role of NLR as an independent predictor of SLE activity. Methods: This was a cross-sectional comparative study conducted in the Department of Physiology, Dhaka Medical College, Dhaka, Bangladesh from July 2016 to June 2017. In this study, 30 SLE patients, aged 18 to 55 years, were considered as the study group and 30 aged matched healthy subjects were considered as control group. SLE Disease Activity Index (SLEDAI) score was used to assess disease activity.NLR and ESR was estimated. Independent samples t-test, Chi Square test, Pearson’s correlation co-efficient (r) test, Regression analysis and ROC curve analysis were performed as applicable. 95% confident interval was calculated and p value <0.05 was accepted as level of significance. Results: In this study, NLR was significantly (p=0.003) higher in SLE patients than control. SLEDAI score was 10 (1-18) and majority (19; 63.33%) of the SLE patients had SLEDAI score >9 (active disease). NLR was significantly (p=0.001) increased more in active SLE than inactive SLE and showed a significant association among NLR and active disease (OR; 6.56, 95% CI; 1.26 to 34.20, p=0.001). NLR was positively correlated with SLEDAI score and ESR in patients with SLE. The optimal NLR cutoff value of 2.2 had 95% sensitivity and73% specificity {AUC = 0.957, 95% CI, 0.892–1.000, p = <0.001}. Conclusion: This study concludes that NLR is significantly increased in SLE patients and can be served as an independent predictor of SLE activity. Bangladesh J Medicine 2023; 34(2): 137-142